PLASTIC TAX IN INDONESIA: A DOUBLE DIVIDEND STRATEGY FOR MARINE POLLUTION REDUCTION AND SUSTAINABLE REVENUE GENERATION - Sulthan A. Nursyahputra; Irfan S. Himawan; Tina Kartini; Ismet Ismatullah (International Journal of Accounting Innovation, 2026)
Objective: Indonesia’s rapid population growth to 288 million in 2025 has driven total waste generation to 36 million t in 2024, with plastics accounting for 20% (around 7 million t) and 65% of plastic waste entering the environment. Marine plastic leakage declined from 615,000 t in 2018 to 350,000 t in 2024, a 41% reduction that falls short of the 70% target for 2025. Method: Employing an explanatory sequential mixed-methods design, this paper first analyzes time-series waste data and conducts document analysis of policy instruments to evaluate a plastic excise tax’s viability. Results: The Ministry of Finance’s proposed Rp30,000/kg rate on plastic tax could generate an estimated IDR 10.50–137.56 trillion in 2024, depending on whether the tax base is defined narrowly around documented marine plastic leakage or more broadly around single-use plastic waste, far exceeding environmental protection allocations that dropped from 18.4% of central spending in 2020 to 0.3% in 2025. Novelty: Grounded in the double-dividend hypothesis, the tax internalizes plastic pollution costs while aiming to support marine protection efforts against marine plastic leakage. Recommendations include immediate implementation with a narrow tax base on single-use plastic bags and/or any specified plastics, legally mandated revenue earmarking for waste infrastructure and marine protection, robust monitoring, and integration with extended producer responsibility to promote circular economy practices and align fiscal policy with Indonesia’s marine debris goals.